Participation in solid waste management: lessons from the Advanced Locality Management (ALM) programme of Mumbai - Anurima Mukherjee Basu; Shruti Punjabi (Journal of Urban Management, 2020)
Swachh Bharat Mission (SBM) is the national flagship programme of the Government of India that aims to achieve the vision of "Clean India'. The Solid Waste Management (SWM) component of the SBM envisages to become a 'janandolan '(people's movement) with participation from a wide range of stakeholders. This assertion emphasizes the importance of community and civic groups in maintaining cleanliness of cities. The 'Advanced Locality Management' Programme (ALM) of Mumbai is one of the earlier efforts of citizen-government partnership for SWM in India. Initiated in 1997 it is still operational in Mumbai. This paper traces the evolution of the ALM programme, with particular reference to engagement of civic groups, their changing roles and responsibilities over time. In doing so, the paper argues that for true 'janandolan' on urban civic issues, a broader mandate for participation that encompasses wider concerns of citizens is required.
Keywords: 710; Advanced locality management (ALM); Mumbai; Participation; Partnership; Solid waste management (SWM)